2010
DOI: 10.1007/s10310-009-0139-3
|View full text |Cite
|
Sign up to set email alerts
|

Can a natural experiment be used as a tool to design partial cutting regimes? The decline of Austrocedrus chilensis forests, an example

Abstract: The forests of Austrocedrus chilensis in Argentina suffer mortality from what is locally known as 'mal del cipre´s'. This disturbance usually appears as aggregations of dead trees of varying sizes. The mortality process seems unpredictable, and regeneration establishment is variable under these conditions. The highly variable mortality rates results in a natural experiment that allows the correlation of overstory mortality with regeneration rate. This correlation should then make it possible to estimate the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 14 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…While previous studies have examined mortality patterns in A. chilensis forests affected by 'mal del ciprés' (Calí, 1996;Loguercio et al, 1998;Relva et al, 2009;Amoroso and Larson, 2010), this study quantifies and describes long-term patterns of overstory mortality at a larger number of stands over several decades using highquality ring-width data. Mortality in A. chilensis forests appears to be unpredictable and variable in time.…”
Section: Mortality Onset and Patternsmentioning
confidence: 98%
See 3 more Smart Citations
“…While previous studies have examined mortality patterns in A. chilensis forests affected by 'mal del ciprés' (Calí, 1996;Loguercio et al, 1998;Relva et al, 2009;Amoroso and Larson, 2010), this study quantifies and describes long-term patterns of overstory mortality at a larger number of stands over several decades using highquality ring-width data. Mortality in A. chilensis forests appears to be unpredictable and variable in time.…”
Section: Mortality Onset and Patternsmentioning
confidence: 98%
“…The presence of this disturbance suggests that these forests could become uneven-aged, but previous studies have shown that the establishment of new individuals in forests under these conditions is highly variable (Loguercio et al, 1998;La Manna et al, 2008b;Relva et al, 2009;Amoroso and Larson, 2010). Successful establishment of A. chilensis in healthy stands occurs in small openings in the canopy and this species is described as having a fine-scale gap-phase regeneration mode (Veblen et al, 1995;Gobbi and Schlichter, 1998;Amoroso and Larson, 2010).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…These approaches emulate natural disturbances in a boreal forest in Canada. Amoroso and Larson (2010) report that the dynamics of stand structure and regeneration in Austrocedrus chilensis stands suffers from cypress sickness (mal del cipre´s). Iijima and Shibuya (2010) clarify suitable regeneration sites for Picea jezoensis on fallen logs accompanied by natural disturbances in sub-boreal forests in Hokkaido, Japan.…”
mentioning
confidence: 99%